SPECTROSCOPIC INVESTIGATIONS OF THE POLARIS (α UMi) SYSTEM: RADIAL VELOCITY MEASUREMENTS, NEW ORBIT, AND COMPANION INFLUENCE FOR THE CEPHEID POLARIS Aa PULSATION ACTIVITY - Usenko, I. A.; Miroshnichenko, A. S.; Danford, S.; Kovtyukh, V. V.; Turner, D. G. (Одеські астрономічні публікації, 2020)
Thirty three spectra of the Polaris system obtained in August–December 2019 and February–April 2020 at the 0.81m telescope of the Three College Observatory (TCO, North Carolina, USA) were used to determine the radial velocities (RV) and effective temperature of the Cepheid Polaris Aa. These new data have been added to the entire Polaris system RV data collection (over 2,500 measurements) to compute a new orbit of the Polaris Aa companion. Furthermore we have used our eight observational datasets taken in 2015–2020 and eight datasets taken in 2011–2018 by Anderson (2019) to check for possible influence of the orbital motion of Polaris Ab on the Polaris Aa pulsational activity. It was found that the mean pulsational period in 2015–2020 was quite stable (3.976±0.012 days), while the pulsational amplitude showed evident changes: a growth before HJD 2457350 with a following decrease. This fact could be due to the Polaris Ab passing through the periastron.